2018
DOI: 10.3390/colloids2040071
|View full text |Cite
|
Sign up to set email alerts
|

Self-Alignment Sequence of Colloidal Cellulose Nanofibers Induced by Evaporation from Aqueous Suspensions

Abstract: Cellulose nanopapers fabricated by drying aqueous colloidal suspensions of cellulose nanofibers (CNFs) have characteristic hierarchic structures, which cause the problem that their optical properties, including their transparency or haze, vary due to the drying processes affecting CNF alignment. It is unclear when and how the colloidal CNFs align in the evaporation–condensation process from the randomly dispersed suspension to form the nanopaper. In this study, we found that the CNFs undergo a self-alignment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…As mentioned earlier, this may be attributable to the longer diffusion times of long CNF particles. Other studies have shown that evaporation/condensation of CNFs can exhibit self-organizing behavior. , Uetani et al observed self-organization of a chiral nematic phase during evaporation and identified the concentration at which the onset of self-organization began at the surface where evaporation was occurring …”
Section: Bottom-up Strategies To Align Cellulose Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, this may be attributable to the longer diffusion times of long CNF particles. Other studies have shown that evaporation/condensation of CNFs can exhibit self-organizing behavior. , Uetani et al observed self-organization of a chiral nematic phase during evaporation and identified the concentration at which the onset of self-organization began at the surface where evaporation was occurring …”
Section: Bottom-up Strategies To Align Cellulose Nanofibersmentioning
confidence: 99%
“…91,92 Uetani et al observed selforganization of a chiral nematic phase during evaporation and identified the concentration at which the onset of selforganization began at the surface where evaporation was occurring. 91 Spinning-Induced Alignment. Fiber spinning comprises an array of fiber formation processes that produce continuous filaments.…”
Section: Bottom-up Strategies To Align Cellulose Nanofibersmentioning
confidence: 99%
“…Densely packed films made of cellulose nanofibers (CNFs) are promising materials for optoelectronics, such as flexible displays and electronic paper, owing to their flexibility and high dimensional stability against the temperature change of each single CNF. , For these optoelectronics, light compensation films, such as polarizers, phase difference films, and backlight films, with large optical anisotropy are essential to control the retardation (i.e., birefringence) owing to polymer chain alignment, , and they are also indispensable to improve the contrast or reduce the rainbow unevenness and light leakage . CNF films are known to show some birefringence when the constitutive CNFs anisotropically align, and CNFs consisting of an extended chain crystal of cellulose molecules are also considered to have large birefringence. , However, the intrinsic birefringence of cellulose, which is the origin to the birefringence of CNF films, greatly varies between cellulose samples, and its estimation represents a bottleneck for producing light compensation films with CNFs to develop high-performance next-generation optoelectronics.…”
mentioning
confidence: 99%
“…However, cast-drying requires a very long drying time, and the casting method results in drying-induced local condensation. Therefore, the evaporation process affects the self-assembly modes of nanocellulose and determines the final film structure (Uetani et al 2018). To avoid lengthy drying and uncontrolled selfassembly, a new high-speed drying technique has recently been developed.…”
Section: Multifunctional Filmsmentioning
confidence: 99%